KOHESI DAN KOHERENSI WACANA NARASI DALAM MODUL KARYA GURU - Darmawati Darmawati (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2012)
This study aims to describe the cohesion and coherence markers that are used to build the integrity of the narrative discourse in Indonesian module composed by the Indonesian language teachers. The research is descriptive qualitative. Research data was sourced from Module Bahasa Indonesia: Jendela Pengetahuan composed by junior high school teachers. The techniques of collecting data were; reading techniques, technical notes, and the techniques of composing corpus. The results showed that: 1) markers of cohesion are used to build the integrity of the narrative discourse consists of: reference, substitution, ellipsis, conjunction, and lexical, 2) the use of coherence markers consist of linkage time, how, conflict, cause and effect, sequences , usability, condition, expressed more meaning.